Juridical Analysis on the Regulation of the Criminal Act of Sexual Abuse from the Perspective of Positive Law - Saputra, Ryan; Risdalina, Risdalina; Kumalasari M, Indra (International Journal Labs, 2024)
Sexual violence against children is a serious problem that affects many aspects of children's lives. Indonesian law, especially Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, regulates legal protection for victims of child sexual violence. This study aims to conduct a juridical analysis of regulations on the crime of sexual harassment from a positive legal perspective. This study uses a normative juridical research approach. The nature of this research is descriptive and analytical. The data used is library research. The results of the study show a. Legal regulations on the protection of children from the crime of sexual harassment are contained in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in Article 15 letters d and e, Article 59 Paragraph (1) and Paragraph (2) letter j, Article 15 A, Article 69A, Article 76E, Article 82 Paragraph (1) and Paragraph (2), and Articles 289-296 of the Criminal Code. b. The form of legal protection for child victims of sexual abuse is realized through Article 69A, which emphasizes that the protection provided to children as victims of sexual abuse. This research contributes to the implementation of legal protection for child victims of sexual abuse in Indonesia, by highlighting the importance of implementing existing regulations and their important role in providing adequate social protection and rehabilitation for victims.